2022
DOI: 10.1002/ep.13929
|View full text |Cite
|
Sign up to set email alerts
|

Design of water‐energy management based on neural networks for an autonomous solar and wind renewable energy system coupled with brackish water desalination

Abstract: In this article, smart water-energy management based on an artificial neural network for a photovoltaic-wind system coupled with water pumping and reverse osmosis desalination unit with hydraulic storage is developed. The proposed system was designed to meet freshwater demand for remote areas of Tunisia's south. The authors focus on an artificial neural network-type management strategy, ensuring power-sharing between sources, hydraulic components, and tank storage. The main objective of the management strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Likewise, annual electrical energy (P m ) can be computed considering Equation (20). The value of net annual electrical energy (Ex e,annual ) is computed as:…”
Section: Estimation Of Yearly Overall Exergymentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, annual electrical energy (P m ) can be computed considering Equation (20). The value of net annual electrical energy (Ex e,annual ) is computed as:…”
Section: Estimation Of Yearly Overall Exergymentioning
confidence: 99%
“…Manchanda et al 18 studied tilted wick solar distillation-cum-dryer experimentally and reported that the cost of distillate was $0.03729/l. Manchanda and Kumar 19 investigated stepped solar still-cum-active dryer experimentally and concluded that the system performed better at lower value of mass flow rate _ m fr ð Þ. Zgalmi et al 20 designed water-energy management by incorporating artificial intelligence and solar desalting unit for getting highest possible freshwater yield for use.…”
mentioning
confidence: 99%